ANALYSIS OF BANK OPERATIONAL PERFORMANCE EFFICIENCY USING OPERATIONAL COST RATIO ON OPERATIONAL INCOME AT PT. BPR CENTRAL SEJAHTERA TANJUNGPINANG - Santi Chen (STIE PEMBANGUNAN TANJUNGPINANG, 2018)
The purpose of this study was to determine the efficiency of operational performance at PT. BPR Central Sejahtera Tanjungpinang by using the BOPO ratio. BOPO is the ratio used to measure the efficiency of the Bank's Operations.The results of this research can be seen that the BOPO ratio at PT.BPR Central Sejahtera tends to increase from 2015 to 2019 in a row 85.16% in 2015, which means that every Rp1 income earned by the bank is Rp. expenses that must be borne by the bank, in 2016 amounted to 81.75%, in 2017 amounted to 83.96%, in 2018 amounted to 84.28% and in 2019 amounted to 85.75% . Based on research results, the operational performance efficiency of PT BPR Central Sejahtera for the period 2015-2019 tends to decline during the 2015-2019 period. Although experiencing an increase in the OEOI ratio, it is still in the Healthy category because the maximum limit of BOPO percentage is above 89%. The increase in BOPO was due to a decrease in Contractual Interest Income.